436 POSTOPERATIVE SYSTOLIC HYPOTENSION IN FRACTURED NECK OF FEMUR PATIENTS. (14th June 2021) - Jones, R; Cook, J; Cannon, A
Abstract: Introduction: Secondary analysis of outcomes after 11, 085 hip fracture operations from the prospective UK Anaesthesia Sprint Audit of Practice (ASAP 2) found an association between reduced intraoperative systolic arterial pressure (SAP) and postoperative mortality at five and 30 days. We sought to determine the incidence of hypotension in the postoperative period, rather than just intraoperatively, in a small sample of patients with fractured neck of femur. Method: We performed a retrospective review of the notes, electronic vital signs and electronic general practice records from 40 patients with fractured neck of femur. We identified the latest SAP performed at their general practice (if done within one year before admission). We noted the pre-operative baseline SAP reading from the ward as well as the lowest SAP during several time periods: the pre-operative period; the fracture surgery; the recovery room; and during each 24-h period postoperatively until the fifth postoperative day. Results: A SAP recording from general practice within the previous year was only accessible in 21 (53%) of patients, but where it was accessible, it was within 20% of the immediate preoperative SAP in 14 (66%) of patients. The incidence of relative hypotension (< 80% preoperative SAP) was 54% in the operating theatre, 41% in the recovery room, 65% on the ward during the remainder of the first postoperative 24 h, 55% during postoperative day 2, 53% during day 3, 33% during day 4 and 41% during day 5. Conclusions: Postoperative hypotension was common in our sample. In our analysis, the highest incidence was on the ward during the first 24 hours postoperatively. However, 41% of patients still had hypotension 5 days postoperatively.